Overlapping and separable activities of BRA-2 and HIM-17 promote occurrence and regulation of pairing and synapsis during Caenorhabditis elegans meiosis - Blazickova, Jitka; Trivedi, Shalini; Bowman, Richard; Sivakumar Geetha, Sowmya; Subah, Silma; Scuzzarella, Michelle; Chang, Alexander; Chandran, Uma R; Yanowitz, Judith L; Smolikove, Sarit; Jantsch, Verena; Zetka, Monique; et al. (Nature communications, 2025)
Faithful meiotic segregation requires pairwise alignment of the homologous chromosomes and their synaptonemal complex (SC) mediated stabilization. Here, we investigate factors that promote and coordinate these events during C. elegans meiosis. We identify BRA-2 (BMP Receptor Associated family member 2) as an interactor of HIM-17, previously shown to promote double-strand break formation. We found that loss of bra-2 impairs synapsis elongation without affecting homolog recognition, chromosome movement or SC maintenance. Epistasis analyses reveal previously unrecognized activities for HIM-17 in regulating homolog pairing and SC assembly in a partially overlapping manner with BRA-2. We show that removing bra-2 or him-17 restores nuclear clustering, recruitment of PLK-2 at the nuclear periphery, and abrogation of ectopic synapsis in htp-1 mutants, suggesting intact CHK-2-mediated signaling and presence of a barrier that prevents SC polymerization in the absence of homology. Our findings shed light on the regulatory mechanisms ensuring faithful pairing and synapsis.
Keywords: Caenorhabditis elegans; synaptonemální komplex; Caenorhabditis elegans Proteins; Mutation; meióza; Meiosis; Cell Cycle Proteins; Chromosome Pairing; Animals; párování chromozomů; Synaptonemal Complex; proteiny buněčného cyklu; zvířata; mutace; proteiny Caenorhabditis elegans